Transforming Politics - Roseneil, S. author. aut Link
XIII, 304 p.
Keywords: This volume examines the transformation of politics and social movements at various levels. Starting with a transformation of identity within social movements, it goes on to discuss changes in the scale of social movement mobilisation. The impact of social movements on the state is also considered, with a particular focus upon the ways in which the state is able to incorporate apparently radical political agendas. Finally, the book examines those intellectual and theoretical debates stimulated by recent political transformations.